2020
DOI: 10.1007/s10900-020-00913-w
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of the COVID-19 Pandemic in the Online Versions of Highly Circulated U.S. Daily Newspapers

Abstract: With the proliferation of news and the abundance of unknowns, COVID-19 information became rife with rumors and infiltrated consumers with confusion and information overload. In situations like this, it is important to provide consumers with credible and reliable information about the pandemic which is affecting their lives and livelihoods. Articles about coronavirus published in online versions of USA Today online, Wall Street Journal online and NYTimes.com between January and March 2020 were identified. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 8 publications
0
36
0
6
Order By: Relevance
“…Therefore, there is a need to better understand people’s views on the use of digital technology to support COVID-19 contact tracing. The COVID-19 pandemic has been widely covered in the media, mirroring the immense public interest, with traditional mass media, including print and online news media, considered to be one of the preferred information sources [ 49 , 50 ]. The dynamic and uncertain situation at the beginning of the pandemic made people particularly reliant on such information sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need to better understand people’s views on the use of digital technology to support COVID-19 contact tracing. The COVID-19 pandemic has been widely covered in the media, mirroring the immense public interest, with traditional mass media, including print and online news media, considered to be one of the preferred information sources [ 49 , 50 ]. The dynamic and uncertain situation at the beginning of the pandemic made people particularly reliant on such information sources.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic and uncertain situation at the beginning of the pandemic made people particularly reliant on such information sources. Previous studies have used media content analyses to assess public debates during the COVID-19 pandemic [ 18 , 50 ], as well as other issues that affect population health [ 51 , 52 ]. Some other studies have combined media content analyses with surveys and interviews [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that those who mostly rely on national news outlets believe that media coverage is largely accurate [ 7 ]. However, national news varies in content and focus; often presents information that is based on the different contexts of pandemics [ 8 , 9 ]; and at times, fails to capitalize on the opportunity to promote infection prevention techniques and coping strategies [ 8 ]. During the time when newspaper content was filled with information on COVID-19, popular social media outlets also began to provide information about the disease [ 10 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from previous epidemics suggests increased coverage and sensational, insensitive or inaccurate reporting can contribute to public fear, moral panic and individual grief [ 12 , 13 ]. Although there has been some attention to the media’s coverage of COVID-19 [ 14 ], only one article has explored the reporting of deaths. Focusing on Bangladeshi reports linking individual deaths to COVID-19, Goni [ 15 ] found this to be a stigmatising practice which resulted in bereaved people facing barriers to bury their loved ones.…”
Section: Introductionmentioning
confidence: 99%